CALL IN READING CLASSROOM: HOW IS CALL IMPLEMENTED BY ESSENTIAL READING LECTURERS? - Yuri Lolita; Marleen M.A.F.Q. Sumampouw; Orestis Soidi (UICELL, 2021)
The aims of this study were to determine the implementation of lecturers about CALL. This study uses a qualitative method with individual interview techniques. Three lecturers teach essential reading which are the samples of this research. There are two, namely: (1) introducing CALL to lecturers and trying to apply it in the reading learning process in class; (2) interviewing lecturers to find out their perception of CALL. Implementation of CALL is an application or computer software as a technology used in learning the context of a second language. The application of Computer Assisted Language Learning (CALL) is one way to develop language teaching practices. The study describes the degree of CALL implementation by Essential Reading Lectures. It applies descriptive qualitative research which is used to discover information on a certain phenomenon. In this research, multiple interviews with open-ended questions were conducted to collect data. Furthermore, the information was analyzed qualitatively by describing the findings supported by relevant theories. The conclusion CALL makes students more enthusiastic in learning English and improves their English skills, especially in terms of reading comprehension. In addition, the application of CALL can improve their skills in using computers for future careers. CALL also provides lecturers to create discussion groups or forums that can be accessed by students. Keywords: CALL (Computer Assisted Language Learning, implementation, Essential Reading Lecturers